Harmonia axyridis (Pallas, 1773) (Coleoptera: Coccinellidae) as a predator of the leaf-galling form of the grape phylloxera Daktulosphaira vitifoliae (Fitch, 1856) (Hemiptera: Phylloxeridae) in Brazil - Oliveira, Daiana da Costa; Andzeiewski, Simone; Bohn, Régis Josué; Moura, Luciano de Azevedo; Bernardi, Daniel; Botton, Marcos (EntomoBrasilis, 2024)
Harmonia axyridis (Pallas, 1773) (Coleoptera: Coccinellidae) is an Asian species intentionally introduced in many countries as a biological control agent for insect pests. In Brazil, it was introduced accidentally and recorded for the first time in Curitiba, Paraná State, in 2002. An inventory of natural enemies of the leaf-galling form of the grape phylloxera Daktulosphaira vitifoliae (Fitch, 1856) (Hemiptera: Phylloxeridae) carried out in Bento Gonçalves, Rio Grande do Sul, the occurrence of predation of all stages of development of D. vitifoliae by larvae and adults of H. axyridis. The presence of H. axyridis preying on D. vitifoliae in vineyards is important because it identifies an exotic species acting as a predator of grape phylloxera populations in Brazil.